The Role of Arisan in Alleviating Household Asset Poverty in Indonesia - Hawari, Muhammad Irsyad; Donna, Duddy Roesmara; Saleh, Samsubar (Jurnal Economia, 2025)
This study explored the impact of participation in Rotating Savings and Credit Associations (ROSCAs) on household asset poverty in Indonesia. It used secondary data from the Indonesia Family Life Survey (IFLS) waves 4 and 5. Asset poverty was measured using indicators from the Socioeconomic Data Collection; households were considered asset poor if they failed to meet nine out of 14 indicators. The analysis applied panel logistic regression with a fixed effects model. The results showed that ROSCA participation significantly reduced the likelihood of asset poverty. These findings supported previous studies that emphasized the positive effect of ROSCAs in reducing expenditure poverty. The study provided empirical evidence of ROSCAs’ role in improving household economic resilience. It suggested that government and related institutions could support and encourage ROSCAs as part of broader poverty reduction and financial security strategies.